Complete start-to-finish MBA admissions guide / Jeremy Shinewald; MbaMission. - Shinewald, Jeremy
"The advice, exercises and multitude of examples included in this guide will help you confidently navigate your way through the entire business school application process and gain that coveted letter of acceptance"--Page 4 of cover.